2019
DOI: 10.18632/aging.102009
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells rejuvenate cardiac muscle through regulating macrophage polarization

Abstract: We have shown that the effects of transplantation of CD146+ mesenchymal stem cells (MSCs) on myocardial regeneration after myocardial infarction (MI) exceeds the effects of transplantation of MSCs, likely resulting from reduction of aging-associated cellular reactive oxygen species in injured cardiac muscle cells (CMCs). Since the role of macrophages in the MSC-mediated recovery of heart function after MI remains unclear, this question was thus addressed in the current study. We found that transplantation of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…44 Both arms of the inflammatory response are required for repair in many systems, such as heart, skeletal muscle, and the central nervous system. 32,41,45,46 Unregulated proinflammatory signals result in premature initiation of the anti-inflammatory cell signals, which can disrupt effective tissue healing. 41 For example, skeletal muscle regeneration is impaired when M F are prematurely activated by treatment with the anti-inflammatory cytokine IL-10.…”
Section: Inflammation and Tissue Regenerationmentioning
confidence: 99%
“…44 Both arms of the inflammatory response are required for repair in many systems, such as heart, skeletal muscle, and the central nervous system. 32,41,45,46 Unregulated proinflammatory signals result in premature initiation of the anti-inflammatory cell signals, which can disrupt effective tissue healing. 41 For example, skeletal muscle regeneration is impaired when M F are prematurely activated by treatment with the anti-inflammatory cytokine IL-10.…”
Section: Inflammation and Tissue Regenerationmentioning
confidence: 99%
“…Macrophages are hypothesized to play a critical role in inflammation by contributing to the exacerbation or reduction of inflammation. Macrophages can differentiate into M1- or M2-like macrophages, which are classically activated macrophages or alternatively activated macrophages [ 8 ] that have polarized phenotypes: pro-inflammatory (M1) or anti-inflammatory (M2). M1 macrophages initiate an inflammatory response and promote T helper cell type 1 (Th1) immunity, which is characterized by the release of proinflammatory cytokines such as tumor necrosis factor (TNF)-α, interferon (IFN)-γ, interleukin (IL)-12, IL-6, and arginase (ARG)-1 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While BMSCs show their therapeutic effects on cardiac remodeling process through paracrine effects, studies have also indicated that immunomodulatory effects can also show their protective effects [9][10][11][12][13][14], such as modulating the function of regulatory T cells (Tregs) and reducing the proliferation of T cells. T cells, a central player in the adaptive immune system, take an important role in affecting acute MI and cardiac remodeling via their proliferation and differentiation [15].…”
Section: Immuno-and Inflammatory Modulation By Bmscs Therapy In Revermentioning
confidence: 99%
“…), with decreased interferongamma (IFN-γ) production, to an anti-inflammatory state with an increase in interleukin 10 (IL-10) production by Tregs [10]. Moreover, BMSCs release antiinflammatory cytokines to affect the macrophage M2 polarization in MI [11]. Of note, inflammation resolution is an important phase for reducing scar formation and protecting cardiac function after MI [16].…”
Section: Immuno-and Inflammatory Modulation By Bmscs Therapy In Revermentioning
confidence: 99%